PENGEMBANGAN HANDOUT BIOTEKNOLOGI SMA DAN SEDERAJAT - Ismi Nurul Qomariyah; Rudy Setiawan (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2016)
Biological as science dominated by memorize, it could be happened because handout or other reference difficult for students. Therefore, we think must create a new handout which help students order to study biological easily. The aims of this research are: (1) get valid and effective high school biological handout; (2) make easy students to understand high school biological materials. The method of this research is develop research. The making of handout based on 4D Thiagarajan model’s, which included four steps, i.e: define, design, develop, and disseminate. Researcher just done until develop step. The result of research are: (1) make a handout biological for high school in biotechnology, (2) make easy students to understand biotechnological.